Pengaruh Literasi Ekonomi Digital dan Kreativitas Mahasiswa Terhadap Minat Berwirausaha Mahasiswa Pendidikan Ekonomi - Sigiro, Yescenia; Surbakti, Eki Monalisa Br; Sitepu , Agnes Dea Lita Br; Angin , Emia Perangin; Sitanggang, Yohanna; Tambunan, Khairuddin Ependi; Adriani, Deni (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to examine the influence of digital economic literacy and creativity on the entrepreneurial interest of Economics Education students, both partially and simultaneously. The study employs a quantitative approach with a causal-associative design. The sample consists of 38 students from the 2022 cohort, selected using proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analysed using multiple linear regression. The results indicate that, when examined partially, digital economic literacy does not have a significant effect on entrepreneurial interest (t = 0.970; p = 0.339 > 0.05), whereas student creativity has a dominant effect and is marginally significant (t = 1.927; p = 0.062). Simultaneously, digital economic literacy and creativity had a significant effect on entrepreneurial interest (F = 3.810; p = 0.032 < 0.05) with a contribution of 17.88%. These findings indicate that creativity is a stronger factor than digital economic literacy in shaping students’ interest in entrepreneurship. The implications of this research emphasise the importance of strengthening creativity-oriented learning through innovative and contextual learning strategies as an effort to enhance the entrepreneurial interest of Economics Education students.